Thermal Behavior Improvement of Fortified Commercial Avocado (Persea Americana Mill.) Oil with Maqui (Aristotelia Chilensis) Leaf Extracts - Echeverria-Morgado, J; Forero-Doria, O (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Avocado oil is considered a highly prized food due to its nutritional contribution. On the other hand, Aristotelia chilensis (Molina) Stuntz (Elaeocarpaceae), common name “maqui”, is an endemic fruit in Chile, well known for its exceptional antioxidant properties. In general, maqui byproducts such as leaves are considered as waste. Thus, maqui leaves extracts were used to improve the stability of vegetable oils, particularly avocado oil. Hence, avocado oil was fortified with two extracts (ethyl ether and methanol) obtained of maqui leaves and exposed to 120 °C for 386 h in an oven. The results showed a high content of monounsaturated fatty acids (69.46%, mainly oleic acid), followed by polyunsaturated fatty acids (16.41%, mainly linoleic acid) and finally saturated fatty acids (14.13%). The concentration of the total phenolic compounds in the pure oil, ethyl ether and methanol maqui leaves extracts were 45.8, 83.7, and 4100.9 ppm, respectively. In addition, the antioxidant activity was 5091.6 and 19,452.5 µmol Trolox eq/g for the ethyl ether and methanol extracts, respectively. The secondary degradation compounds showed significant differences between the fortified and non-fortified samples after 144 h and the TG/DTG analysis showed a significant increment of 7 °C in the degradation temperature (Tonset) of avocado oil fortified with the methanol extract when compared to the non-fortified oil and fortified oil with ethyl ether extract. After heating for 336 h, fortified oil with methanol extract reached the limit percentages of polar compounds, while pure oil reached it in a shorter time, i.e., 240 h. Based on the results, avocado oil can be protected with natural additives such as extracts obtained from maqui leaves, leading to an increase in its thermo-oxidative stability. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.